Iteration-complexity of the subgradient method on Riemannian manifolds with lower bounded curvature. (3rd April 2019) - Ferreira, O. P.; Louzeiro, M. S.; Prudente, L. F.
Abstract: The subgradient method for convex optimization problems on complete Riemannian manifolds with lower bounded sectional curvature is analysed in this paper. Iteration-complexity bounds of the subgradient method with exogenous step-size and Polyak's step-size are stablished, completing and improving recent results on the subject.